Clean Air Act Issues in the 108th Congress. (U.S. Congressional Research., 2003)
Examines various Clean Air Act (CAA) proposals and issues in the 108th Congress, including EPA proposed changes to CAA new source review requirements, multi-pollutant legislation, methyl tertiary butyl ether gasoline additive, conformity of metropolitan area transportation plans and State implementation plans, and deadlines for ozone air quality standards achievement.